Photothermal therapy combined with a STING agonist induces pyroptosis, and gasdermin D could be a new biomarker for guiding the treatment of pancreatic cancer - Yanyan Hu; ErPeng Qi; Chao Yun; Xi Li; Fangyi Liu; Zhigang Cheng; Na Guan; Qiong Wang; Huixia Zhao; Wenhua Xiao; Liang Peng; Jingwen Yang; et al. (Journal of Translational Medicine)
Abstract Purpose Although photothermal therapy (PTT) can induce antitumour immunity, the mechanisms underlying its effects in pancreatic cancer (PC) require further exploration. In this study, the mechanism of action of PTT and its connection to pyroptosis as well as the therapeutic potential of PTT alone and in combination with STING agonists, were investigated. In addition, a biomarker of PC was found to stratify patients who are suitable for PTT. Experimental design We explored whether PTT can induce pyroptosis in vitro and evaluated the therapeutic efficacy and antitumour immunity-inducing ability of PTT combined with STING agonist (c-di-GMP) as immune adjuvant in vivo in PC. We also evaluated gasdermin D (GSDMD) expression in tumour tissues and investigated drug sensitivity in patient-derived organoids (PDOs) with differential GSDMD expression. Results Our study demonstrated that local PTT induces pyroptosis via the caspase-1/GSDMD pathway and elicits antitumour immunity. PTT combined with a STING agonist exhibits better therapeutic efficacy than PTT alone while limiting distant tumour metastasis, and enhances the immune response by promoting dendritic cell maturation, increasing the frequency of tumour infiltrating T cells, and converting macrophages from the M2 to the M1 phenotype. In addition, we found that GSDMD is highly expressed in tumour tissues and that overexpression of GSDMD in PC might suggest increased resistance to chemotherapy and the potential benefits of local therapy. We further confirmed that PDOs with higher GSDMD expression are less sensitive to a chemotherapeutic agent (5-Fluorouracil) than PDOs with lower GSDMD expression, making GSDMD a new biomarker for identifying patients who may benefit from PTT. Conclusions In this work, c-di-GMP was used as an immune adjuvant for PTT to treat PC for the first time, and the results provide clues for the development of novel combination immunotherapies that simultaneously suppress primary tumours and distant metastases. GSDMD has great potential as a new biomarker for the selection of individualized treatment modalities.